Oxidation resistance of carborane-containing polymer coatings for carbon–carbon composites at low and medium temperatures. (1st July 2019) - Pan, Yunxing; Cheng, Shengli; Dong, Hang; Li, Nan; Bao, Feng; Wang, Jinyan; Jian, Xigao
Graphical abstract: Highlights: Polymer-based oxidation-resistance coatings were prepared on C/C composites. Effect of inorganic fillers on oxidation behaviour of polymer coatings is studied. Coatings were fabricated by simple preparation technique and low temperature curing. The polymer-based coatings can be applied to large-scale structures. The good oxidation resistance is due to the formation of borosilicate glasses. Abstract: A novel oxidation resistant thermoset polymer (MSCB) with excellent thermo-oxidative stability and good solubility was designed and synthesized. To prevent C/C composites from oxidation, a series of MSCB polymer-based coatings were prepared by precursor infiltration and thermal-curing at 300 ℃. The oxidation behaviour of the MSCB-, MSCB/TiO2 -, MSCB/ZrO2 - and MSCB/SiC-coated C/C composites was studied. The improved oxidation resistance of the C/C composites was attributed to the good adhesion of the coatings and the formation of a borosilicate protective layer on the surface of the coatings, which was confirmed by the results of TGA, SEM, XPS, and XRD analyses.